Glatiramer Acetate Treatment-Related Effects on Visual EPs and P300 Wave in Patients Suffering from Multiple Sclerosis - Major, Z.Z.; Văcăraş, V.; Buzoianu, A.D; Mureşanu, D.F. (Нейрофизиология, 2013)
Multiple sclerosis is an inflammatory neurological disease of young adults that leads to numerous therapeutic problems and to severe disability. Glatiramer acetate (GA) is a diseasemodifying drug used frequently for long-term treatment of the disease. We investigated the impact of GA treatment on the parameters of reversal-pattern visual evoked potentials and event-related P300 wave (reflecting visual acuity and cognitive dysfunction). Relapsingremitting multiple sclerosis patients either subjected to one-year-long continuous treatment with GA or without any disease-modifying therapy and also healthy controls were involved in the study. The above-mentioned parameters were analyzed at two time points, at the first recording and after one year. It was found that GA did not exert a significant influence on the phenomena studied at least during the one-year follow-up. This finding is in contrast to most of the clinical observations. Розсіяний склероз – запальне неврологічне захворювання, від якого страждають молоді люди, яке спричиняє численні терапевтичні проблеми і призводить до тяжкої інвалідизації. Глатирамер ацетат (ГА) є одним із препаратів, що модифікують захворювання, і використовується часто для впливають на захворювання; він часто використовується для лікування пацієнтів із такою патологією. Ми досліджували вплив лікування із застосуванням ГА на параметри зорових ВП, які виникали після пред’явлення реверсивного патерну, та пов’язаного з подією потенціалу P300 (що відбивають гостроту зору та когнітивну дисфункцію відповідно). Пацієнти, які страждали від розсіяного склерозу (ті, що пройшли однорічний безперервний лікувальний курс із застосуванням ГА, та ті, що не піддавалися такій терапії, модифікуючій захворювання), і здорові суб’єкти (контроль) брали участь у дослідженні. Згадані параметри аналізували у двох моментах часу – при першій реєстрації та через рік. Виявлено, що ГА не демонстрував істотних ефектів щодо параметрів, що вивчалися, в усякому разі в межах одного року. Цей факт супер